2017
DOI: 10.3389/fnagi.2017.00222
|View full text |Cite
|
Sign up to set email alerts
|

Age and Chronicity of Administration Dramatically Influenced the Impact of Low Dose Paraquat Exposure on Behavior and Hypothalamic-Pituitary-Adrenal Activity

Abstract: Little is known of the age-dependent and long-term consequences of low exposure levels of the herbicide and dopaminergic toxicant, paraquat. Thus, we assessed the dose-dependent effects of paraquat using a typical short-term (3 week) exposure procedure, followed by an assessment of the effects of chronic (16 weeks) exposure to a very low dose (1/10th of what previously induced dopaminergic neuronal damage). Short term paraquat treatment dose-dependently induced deficits in locomotion, sucrose preference and Y-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 53 publications
(64 reference statements)
3
25
2
Order By: Relevance
“…It is therefore possible that this injection protocol did not have the potency required to induce a significant amount of degeneration. However, a similar 6 injection procedure has been employed by other studies, and has been able to elicit significant neurodegenerative effects (Jiao et al, 2012;Rudyk et al, 2017;Thiruchelvam et al, 2003), allowing for the possibility that it is other factors that are responsible for this difference.…”
Section: Increased Oxidative Stress and Homocysteine Levels In Striatmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore possible that this injection protocol did not have the potency required to induce a significant amount of degeneration. However, a similar 6 injection procedure has been employed by other studies, and has been able to elicit significant neurodegenerative effects (Jiao et al, 2012;Rudyk et al, 2017;Thiruchelvam et al, 2003), allowing for the possibility that it is other factors that are responsible for this difference.…”
Section: Increased Oxidative Stress and Homocysteine Levels In Striatmentioning
confidence: 99%
“…It has been shown to alter NE signalling in the locus coeruleus (LC), paraventricular nucleus (PVN) of the hypothalamus, and hippocampus (Litteljohn, Mangano, Shukla, & Hayley, 2009;Litteljohn, Nelson, Bethune, & Hayley, 2011;Rudyk, Litteljohn, Syed, Dwyer, & Hayley, 2015). Decreased 5-HT in the medial prefrontal cortex (mPFC) and dorsal hippocampus has been demonstrated following paraquat treatment (Litteljohn et al, 2009), as well as reductions in glucocorticoid receptors in the hippocampus (Rudyk et al, 2017).…”
Section: Paraquat and Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…The present thesis experiments seek to investigate the pesticide, paraquat, either alone or in combination with the inflammatory endotoxin, LPS. Previous work in our laboratory has substantially explored these models, and found them to elicit highly reproducible PD-like behavioral and biological pathology [42,48,50,[139][140][141]. Meta-analyses and epidemiological studies primarily conducted on agricultural communities have demonstrated a strong link between pesticides and PD in humans [142][143][144].…”
Section: Environmental Hit Pd Modelingmentioning
confidence: 99%
“…In fact, the highest levels of LRRK2 were found in peripheral lymphocytes and monocytes of PD patients [323] and LRRK2 mutations have been associated with microglial reactivity and pro-inflammatory cytokine production in the brain and periphery [278,[324][325][326]. Moreover, typical inflammatory agents, such as lipopolysaccharide (LPS), as well as chemical toxicants like MPTP, that are used to model PD pathology, have been shown to influence processes linked to LRRK2 [104,140,327].…”
Section: Introductionmentioning
confidence: 99%